Genome-wide identification, in-silico characterization, and expression analysis of polygalacturonases in different fungal species - Laiba Amin; Imran Zafar; Adil Jamal; Syed M. Safeer Mehdi Bokhari; Fayez Saeed Bahwerth; Muhammad Noman (Molecular Genetics and Genomics, 2026)

Dual Inhibition of PTP1B and DPP-IV by Metabolites from Artocarpus elasticus Leaves Enhances Insulin Signaling and Sensitivity - Abdul Bari Shah; Muhammad Tayyab Khan; Safeer Ullah; Aizhamal Baiseitova; Muhammad Idrees; Il-Keun Kong; Ki Hun Park (Journal of Pharmaceutical Innovation, 2026)

Interfacial Stabilization and Geochemical Transformation of Antimony in Contaminated Soil Using a Ferrihydrite-Functionalized Biochar–Montmorillonite Composite - Rabia Safeer; Guijian Liu; Balal Yousaf; Aniqa Ashraf; Muhammad Irtaza Sajjad Haider; Samra Ijaz; Ruijia Liu (International Journal of Environmental Research, 2026)

Socioeconomic drivers and farmers’ perception of climate change impact on agroforestry adoption: a regression-based study in South Punjab, Pakistan - Muhammad Safeer; Muhammad Zubair; Tanveer Hussain; Muhammad Ammar Khan; Muhammad Madnee; Turkan Hasanova Allahverdi (Agroforestry Systems, 2026)

EPIGENETIC REDUCTION OF H3K9me3 AND H3K27me3 BY RK-701 AND GSK 126 IMPROVES THE DEVELOPMENTAL COMPETENCE OF BOVINE SCNT EMBRYOS - Deborah Onosetale; Zaheer Haider; Chalani Dilshani Perera; Safeer Ullah; Seo-Hyun Lee; Seung-Eun Lee; Jihyo Kim; Min-Ju Lee; Muhammad Idrees; Il-Keun Kong (Theriogenology, 2026)

Trichoderma Enhance Soil Properties in Fusarium Infested Soil and Increase Mineral Nutrients of Chickpea Grains: Findings from Field Experiments - Safeer Akbar Chohan; Muhammad Akbar; Muhammad Asad Farooq; Nasim Ahmad Yasin; Umer Iqbal; Tayyaba Khalil (Journal of Soil Science and Plant Nutrition, 2026)

Fabrication, Characterization, and Effects of CuS Nanoparticles as Nano-Fertilizers on the Morphological, Biochemical Responses, and Bioaccumulation of Metal in Soybean (Glycine Max L.) and Sesame (Sesamum Indicum L.) - Jehangir Khan; Anila Sajjad; Khalid Khan; Ihsan Ullah; Syed Hamza Safeer; Muhammad Zia (Journal of Soil Science and Plant Nutrition, 2026)

Climatic variability linkages with agroforestry adoption in Pakistan: a socio-ecological review - Muhammad Safeer; Muhammad Zubair; Tanveer Hussain; Muhammad Ammar Khan; Muhammad Madnee (Agroforestry Systems, 2025)

Sustainable cementless concrete reinforced with recycled steel fibers for spun-cast precast pipes: an innovative solution - Safeer Abbas; Moncef Nehdi; Ali Ahmed; Muhammad Abdullah Khan; Muhammad Mubashir Ajmal; Ammad Amir; Muhammad Zain Kashif; Qura tul Ain (Innovative Infrastructure Solutions, 2025)

Functionalized biochar with enhanced interfacial properties for synergistic adsorption and photodegradation mechanisms of levofloxacin in industrial effluents - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Aniqa Ashraf; Rabia Safeer; Samra Ijaz; Ruijia Liu (Process Safety and Environmental Protection, 2025)

Microplastic contamination in agricultural soils from mulch films and organic amendments: Transformation mechanism, soil-Biota toxicity, and future perspectives - Bisma Sattar; Guijian Liu; Balal Yousaf; Muhammad Arif; Muhammad Zeeshan Gulzar; Muhammad Irtaza Sajjad Haider; Rabia Safeer; Samra Ijaz; Muhammad Awais Haider; Kiran Aziz (Waste Management, 2025)

Landslide susceptibility mapping using artificial intelligence models: a case study in the Himalayas - Muhammad Afaq Hussain; Zhanlong Chen; Yulong Zhou; Sansar Raj Meena; Nafees Ali; Safeer Ullah Shah (Landslides, 2025)

Organic matter and microplastics nexus: A comprehensive understanding of the synergistic impact on soil health - Samra Ijaz; Guijian Liu; Abdul Rehman; Muhammad Irtaza Sajjad Haider; Rabia Safeer; Bisma Sattar; Muhammad Zeeshan Gulzar; Sofia Nosheen; Balal Yousaf (Science of The Total Environment, 2025)

Hydrothermal integrated chemical treatment of microplastics for efficient degradation: Mechanistic insight and degradation behavior - Muhammad Zeeshan Gulzar; Guijian Liu; Balal Yousaf; Muhammad Imran; Muhammad Arif; Muhammad Nauman; Muhammad Irtaza Sajjad Haider; Bisma Sattar; Rabia Safeer; Samra Ijaz; Ruijia Liu (Journal of Water Process Engineering, 2025)

Green product development (GPD): a systematic literature review and future research directions - Hafiz Muhammad Usman Khizar; Kinaan Khalid; Safeer Haider; Jingbo Yuan (Environment, Development and Sustainability, 2024)

Synergistic interactions and reaction mechanisms of biochar surface functionalities in antibiotics removal from industrial wastewater - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Kiran Aziz; Aniqa Ashraf; Rabia Safeer; Samra Ijaz; Krzysztof Pikon (Environmental Pollution, 2024)

Insights into the biogeochemical transformation, environmental impacts and biochar-based soil decontamination of antimony - Rabia Safeer; Guijian Liu; Balal Yousaf; Aniqa Ashraf; Muhammad Irtaza Sajjad Haider; Ayesha Imtiyaz Cheema; Samra Ijaz; Audil Rashid; Anila Sikandar; Krzysztof Pikoń (Environmental Research, 2024)

The development of plastic waste and sewage sludge co-pyrolyzed biochar composites with improved interfacial characteristics for the effective removal of ciprofloxacin - Aniqa Ashraf; Guijian Liu; Muhammad Arif; Balal Yousaf; Pervaiz Akhtar; Audil Rashid; Humaira Gulzaman; Rabia Safeer; Muhammad Saqib Rashid; Muhammad Irtaza Sajjad Haider (Process Safety and Environmental Protection, 2024)

NGS-driven molecular diagnosis of heterogeneous hereditary neurological disorders reveals novel and known variants in disease-causing genes - Ayaz Khan; Shixiong Tian; Muhammad Tariq; Sheraz Khan; Muhammad Safeer; Naimat Ullah; Nazia Akbar; Iram Javed; Mahnoor Asif; Ilyas Ahmad; Shahid Ullah; Humayoon Shafique Satti; et al. (Molecular Genetics and Genomics, 2022)

Synthesis, theoretical investigations and biological evaluation of ibuprofen drug hybrids - Adina Tatheer; Shahzad Murtaza; Naghmana Kausar; Ataf Ali Altaf; Samia Kausar; Safeer Ahmed; Shabbir Muhammad; Amjad Hussain (Medicinal Chemistry Research, 2022)

The molecular genetics of human appendicular skeleton - Safeer Ahmad; Muhammad Zeeshan Ali; Muhammad Muzammal; Fayaz Ahmad Mir; Muzammil Ahmad Khan (Molecular Genetics and Genomics, 2022)

A novel protein truncating mutation in L2HGDH causes L-2-hydroxyglutaric aciduria in a consanguineous Pakistani family - Muhammad Muzammal; Muhammad Zeeshan Ali; Beatrice Brugger; Jasmin Blatterer; Safeer Ahmad; Sundas Taj; Syed Khizar Shah; Saadullah Khan; Christian Enzinger; Erwin Petek; Klaus Wagner; Muzammil Ahmad Khan; et al. (Metabolic Brain Disease, 2022)
Background L-2-hydroxyglutaric aciduria (L2HGA) is a rare neurometabolic disorder that occurs due to accumulation of L-2-hydroxyglutaric acid in the cerebrospinal fluid (CSF), plasma and urine. The clinical manifestation of L2HGA includes intellectual disability, cerebellar ataxia, epilepsy, speech problems and macrocephaly. Methods In the present study, we ascertained a multigenerational consanguineous Pakistani family with 5 affected individuals. Clinical studies were performed through biochemical tests and brain CT scan. Locus mapping was carried out through genome-wide SNP genotyping, whole exome sequencing and Sanger sequencing. For in silico studies protein structural modeling and docking was done using I-TASSER, Cluspro and AutoDock VINA tools. Results Affected individuals presented with cognitive impairment, gait disturbance, speech difficulties and psychomotor delay. Radiologic analysis of a male patient revealed leukoaraiosis with hypoattenuation of cerebral white matter, suggestive of hypomyelination. Homozygosity mapping in this family revealed a linkage region on chromosome 14 between markers rs2039791 and rs781354. Subsequent whole exome analysis identified a novel frameshift mutation NM_024884.3:c.180delG, p.(Ala62Profs*24) in the second exon of L2HGDH . Sanger sequencing confirmed segregation of this mutation with the disease phenotype. The identification of the most N-terminal loss of function mutation published thus far further expands the mutational spectrum of L2HGDH.

The influence of personality traits on sustainability-oriented entrepreneurial intentions: the moderating role of servant leadership - Sajjad Nawaz Khan; Muhammad Mubushar; Ikram Ullah Khan; Hafiz Mudassir Rehman; Safeer Ullah Khan (Environment, Development and Sustainability, 2021)